A Case of Examination Anxiety in an Adult - Blum, Donna M. (Canadian Journal of Counselling and Psychotherapy, 1972)
One female undergraduate college student served as the sole subject, selected on the basis of verbal reports of extreme test anxiety as well as scores on the Fear Inventory and responses to the Revised Willoughby Questionnaire for Self-Administration. The total treatment process, including both relaxation training and desensitization, required 29 one-half hour sessions. A significant decrease in reported test anxiety occurred. The reported changes were reflected on course examinations and final grades. In addition, the subject had disclaimed any apprehension or feelings of anxiety as the final examinations drew near. Thus, in keeping with a learning theory approach, it is postulated that fear of examinations was a learned maladaptive pattern of behavior. Therefore, counterconditioning through progressive relaxation and systematic desensitization was utilized to eliminate the maladaptive response.